Grundtvig og den første folkehøjskoles mænd - Skovmand, Roar (Grundtvig-Studier, 1960)
Grundtvig and the men of the first folk high school. By Roar Skovmand. Grundtvig not only originated the idea behind the folk high-school, but, from the very beginning, followed the realization of the idea with great attention. When, in 1844, the founding of the first folk high-school at Rødding in South Jutland was decided upon, Grundtvig welcomed the school in a great speech delivered at a public meeting - till then the largest held in Denmark – at Skamlingsbanken. He admitted, it is true, that he had in mind something different, - a State high-school at Sorø that would gather together youth from all sections of the nation; but he regarded the new school, the primary task of which was to safeguard Danish civilization against the encroachments of the German neighbour, as a “giant stride” in the right direction, and he promised to follow and support the work of this school. However, he found it difficult to keep his promise. Travel conditions in those days meant that Rødding was so far from Copenhagen that Grundtvig, though he received many invitations, never visited it, just as, indeed, he failed to visit other high-schools situated beyond the area of the capital. Nevertheless, there was a constant connection between Grundtvig and the men of the first folk high-school. The founder of the school, Professor Christian Flor, was one of Grundtvig’s most independent and most considerable disciples. In the spirit of Grundtvig, he stressed at the Rødding school the importance of history and literature, neglecting subjects of practical, technical value. There was, however, no close personal contact between Flor and Grundtvig. Flor once characterized Grundtvig as the monumental figure that indicated the goal and the way to it. Of the principals and teachers that had led the school in the period prior to 1864, three were closely associated with Grundtvig: Sofus Høgsbro, principal from 1850- 62, was a personal friend of Grundtvig’s eldest sons and a frequent guest in his home. He was not only an independent disciple of Grundtvig, but a man of stubborn character who did not deter from contradicting the old man when he was too one-sided, and he succeeded in influencing him politically towards radicalism. In ecclesiastical matters he agreed with Grundtvig, without sharing his religious conceptions. Although Grundtvig, in a sense, ranked him higher as a politician than as a high-school man, he supported Høgsbro in his controversy at the school with Edv. Thomsen, the natural science teacher, who wanted the school to cater to the technical needs of prospective farmers. During this conflict Grundtvig consented to join a triumvirate which was to appoint persons for the leadership of the school. Unlike Høgsbro his other fellow-teacher, Jens Lassen Knudsen, the father of Jakob Knudsen, the writer, maintained that the school should be a Grundtvigian school aiming at rousing young people, spiritually and intellectually, - like Christen Kold’s high-school on the island of Funen. Høgsbro would not agree to this, and this second conflict at Rødding did not end until Ludvig Schrøder, a young theologian, became leader of the school in 1862. He was as much impressed by Grundtvig’s Christian and liberal adult educational ideas as Knudsen was, and was at first so strongly influenced by them that even Grundtvig became anxious about his eagerness; but Schrøder proved wise enough to strike a balance between the traditions from the school of Flor and Høgsbro and the one-sided ideals set up by Knudsen and Kold. When the Germans had conquered South-Jutland in 1864 and the Røddingteachers moved to Askov, north of the new border, Schrøder called his new school »Flors High-School«, but the Grundtvigian impress it bore was so strong that it became the centre of the Grundtvigian high-school in Denmark. Grundtvig’s relation to the Danish folk high-school was never closer than this school was to him.